2021
DOI: 10.1155/2021/7644648
|View full text |Cite
|
Sign up to set email alerts
|

Shexiang Baoxin Pill for Acute Myocardial Infarction: Clinical Evidence and Molecular Mechanism of Antioxidative Stress

Abstract: Acute myocardial infarction (AMI) has been a preclinical and clinical concern due to high hospitalization rate and mortality. This study was aimed at evaluating the effectiveness and safety of Shexiang Baoxin Pill (SBP) for AMI and exploring the possible mechanism of oxidative stress. Six databases were searched on March 26, 2021. Twenty-four studies were included and accessed by the RoB 2.0 or SYRCLE tool. Compared with routine treatment (RT), SBP showed the effectiveness in the clinical efficacy ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…As the development of AF seems to be a result of the combination of a plethora of risk factors and comorbidities, oxidative stress has been associated with incident AF, while oxidative stress-induced atrial remodeling is considered the most common underlying mechanism; according to several reports, hyperhomocysteinemia has been linked with endothelial dysfunction, thus it represents an important factor for cardiovascular morbidity and mortality [ 93 , 94 ]. We were able to locate a total of 26 reports assessing oxidative stress as a potential mechanism of Hcy-induced cardiotoxicity [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 48 , 49 , 50 , 95 ]. Of these, 25 trials reported a positive correlation between Hcy and cardiomyocyte oxidative stress, while only one report failed to demonstrate oxidative stress as a cause of electron transport chain dysfunction, possibly due to an increased expression of the other protective mitochondrial proteins [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…As the development of AF seems to be a result of the combination of a plethora of risk factors and comorbidities, oxidative stress has been associated with incident AF, while oxidative stress-induced atrial remodeling is considered the most common underlying mechanism; according to several reports, hyperhomocysteinemia has been linked with endothelial dysfunction, thus it represents an important factor for cardiovascular morbidity and mortality [ 93 , 94 ]. We were able to locate a total of 26 reports assessing oxidative stress as a potential mechanism of Hcy-induced cardiotoxicity [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 48 , 49 , 50 , 95 ]. Of these, 25 trials reported a positive correlation between Hcy and cardiomyocyte oxidative stress, while only one report failed to demonstrate oxidative stress as a cause of electron transport chain dysfunction, possibly due to an increased expression of the other protective mitochondrial proteins [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Modern pharmacological studies have proven that L. orientalis Mill. possesses potent anti-inflammatory effects, neuroprotective effects, anti-cancer effects, and antioxidant effects ( Guo et al, 2021b ; Liu et al, 2021 ). The components of this prescription can promote the disappearance of herpes in patients with severe herpes eruptions.…”
Section: Discussionmentioning
confidence: 99%
“…TLR4 is most important in the Suhexiang-Bingpian PPI network (degree = 12). Volatile oils with aromatic resuscitation can improve blood circulation and reduce platelet aggregation [47,48]. In view of molecular mechanism against AS, volatile oils inhibited TLR4 for reducing the secretion of inflammatory factor PTGS2, and improved the stability of atherosclerotic plaques [49].…”
Section: Honghua-taorenmentioning
confidence: 99%